Incomplete Kawasaki Disease in an Elderly Man - Gilles Safa; Clémence Saillard; Laure Darrieux (Karger Publishers, 2013)
Kawasaki disease (KD) is a systemic vasculitis of unknown etiology, affecting predominantly young children. Here, we describe an unusual case of a 75-year-old man with several unique features of incomplete KD. Healthcare professionals should therefore be aware of the importance of considering KD at any age, even among elderly individuals. This case also highlights the usefulness of the algorithm proposed for children to diagnose incomplete KD in adults.